Preparation, Characterization of A New Cis – Iodoplatin and Cis - Carboplatin Complexes and Study There Spectral, Physical and Pharmaceutical Properties (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This search includes preparation of new cis–platin, in the form of iodin, and new two cis - carboplatin complexes {cis  [Pt(4-aminoantipyrine) (NH3)2]I2 and cis[Pt (aminosalicylicacid) (NH3)2]I},   which used as anti - cancer drugs, they are prepared by using the organic ligands 4-amino salicylic acid and 4-amino anti pyrine. These complexes were characterized by using UV–Vis., FTIR, XRD and 1HNMR spectroscopic techniques . The effect of the concentration and the temperature on the molar electrical conductivity of its solutions were studied. The expiry date (half-life) for the solutions of the complexes in the circumstances at the degrees (350C) and (20 0C) was determined